Palha de Urochloa ruziziensis no manejo da gomose (Phytophthora nicotianae) em pomares cítricos - Mendes, Gustavo Luiz (Universidade Federal de São Carlos, 2018)
ABSTRACT Brazilian citriculture is the global leader in orange production and export, but it faces serious phytosanitary challenges, such as gummosis caused by Phytophthora nicotianae. In pursuit of sustainable management practices, soil cover with Urochloa ruziziensis has gained attention for its benefits to soil quality and potential to suppress pathogens. In this context, the objective of this study was to evaluate the effect of U. ruziziensis straw on gummosis management, aiming to contribute to the development of more sustainable and efficient agricultural practices for disease control. The experiment was conducted in pots with ‘Cravo’ lemon seedlings, using soil from areas with six years of ecological or conventional mowing, with or without the addition of U. ruziziensis straw (mulching), and with or without inoculation of P. nicotianae. A randomized block design was adopted, in a 2×2×2 factorial scheme, with six replicates. After 62 days of inoculation, plant height, stem diameter, shoot and root dry mass, and disease severity (length and width of stem lesions) were evaluated. Data were subjected to analysis of variance, and means were compared by Tukey's test at 5% significance. Plants grown in soil from areas managed with ecological mowing showed greater height growth, higher shoot dry mass, and lower disease severity. Mulching addition proved beneficial when applied to soils under conventional management, increasing stem diameter and root dry mass without intensifying gummosis severity. It is concluded that ecological mowing and the use of U. ruziziensis are promising practices to integrate into sustainable gummosis management strategies in citrus.
Urochloa ruziziensis straw in the management of gummosis (Phytophthora nicotianae) in citrus orchards
Keywords: Doença; Cobertura vegetal; Manejo integrado; Sustentabilidade; Disease; Vegetation cover; Integrated management; Sustainability; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA